PENGARUH TIME BUDGET PRESSURE, KONFLIK PERAN DAN PEMAHAMAN GOOD GOVERNANCE PADA KINERJA AUDITOR DI INSPEKTORAT PROVINSI BALI - Ni Putu Devy Rismayanti; Putu Nuniek Hutnaleontina (UNHI Press, 2020)
Auditor performance is the work achieved by the auditorf in carrying out his duties based on the responsibilities given to him and becomes one off thef benchmarks in assessing whether thef work done by an auditor is goodf or vice versa. Generally thef decline in auditorf performance occurs due tof several factors such as pressuref and different instructions for completingf thef auditf. This study aims tof determine the time budget pressure, role conflict and comprehension of good governancef towards performance off the auditor in Inspectorate off Balif Province. Thef population off this study were all functional position auditor and all officials off local government affairs in Inspectorate of Bali Province and the samplingf method was using saturated or census sample method. This study used a sample of 56 respondents. Data analysis techniques used in this study is Multiple Linear Regression. Based on thef results off this study, it can be seen thatf timef budget pressure and role conflict have a significant negative effect on auditor performance. While comprehension of good governance has a significant positive effect on auditor performance.